2016
DOI: 10.1038/ncomms11278
|View full text |Cite
|
Sign up to set email alerts
|

Signalling couples hair follicle stem cell quiescence with reduced histone H3 K4/K9/K27me3 for proper tissue homeostasis

Abstract: Mechanisms of plasticity to acquire different cell fates are critical for adult stem cell (SC) potential, yet are poorly understood. Reduced global histone methylation is an epigenetic state known to mediate plasticity in cultured embryonic SCs and T-cell progenitors. Here we find histone H3 K4/K9/K27me3 levels actively reduced in adult mouse skin and hair follicle stem cells (HFSCs) during G0 quiescence. The level of marks over specific gene promoters did not correlate to mRNA level changes in quiescent HFSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(79 citation statements)
references
References 53 publications
(104 reference statements)
12
67
0
Order By: Relevance
“…Intriguingly, these data are in line with the data from cultured ESCs (1) where ESCs, compared to more lineage-restricted cell types, showed the highest exchange rates of histone proteins. Moreover, these data agree with our previous report, in which quiescent HFSCs have been shown to have globally reduced histone epigenetic marks (9), another chromatin feature associated with higher plasticity in ESCs and T cell progenitors (10, 11). …”
supporting
confidence: 93%
See 3 more Smart Citations
“…Intriguingly, these data are in line with the data from cultured ESCs (1) where ESCs, compared to more lineage-restricted cell types, showed the highest exchange rates of histone proteins. Moreover, these data agree with our previous report, in which quiescent HFSCs have been shown to have globally reduced histone epigenetic marks (9), another chromatin feature associated with higher plasticity in ESCs and T cell progenitors (10, 11). …”
supporting
confidence: 93%
“…Hypomethylation of H3 K9/27me3 has been previously associated with increased cell fate plasticity in ESCs and in quiescent T-cells in vitro (10, 11). We found that this specialized chromatin state accompanies differential regulation of multiple histone methylases and demethylases, and is associated with BMP signaling (9), previously shown to be critical for proper maintenance of quiescent state (12). Moreover, blocking the establishment of hypomethylation at catagen via chemical inhibition of H3 K4/9/27 methylases led to a pronounced delay in anagen onset.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Further in vitro studies showed that Jmjd3 (H3K27me3 demethylase) activation leads to premature epidermis differentiation, whereas Jmjd3 depletion failed to activate epidermal differentiation genes in human keratinocytes . In the bulge, we found that Ezh2 mRNA is downregulated at catagen, whereas Ezh1 remains expressed . Intriguingly, a small subset of genes acquires H3K27me3 marks at catagen, as demonstrated by our Chip‐Seq analysis .…”
Section: Histone Methylation In Skin Development and Homeostasissupporting
confidence: 64%